QUIET QUITTING, BURNOUT, DAN GREAT RESIGNATION PADA LINGKUNGAN KERJA KORPORASI - Isra Puspita Hardani (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the relationship between quiet quitting, burnout, and great resignation, as well as to identify the role of employer branding in influencing these phenomena. This study employs a literature review approach by analyzing various scientific articles and industry reports relevant to burnout, quiet quitting, great resignation, and employer branding that meet the inclusion criteria and are aligned with the research objectives. The findings indicate that burnout can trigger quiet quitting, which subsequently increases employees’ tendency to resign from their jobs. The main factors underlying these phenomena include the mismatch between employer promises and employees’ actual work experiences, limited career development opportunities, unsupportive workplace relationships, and a lack of work flexibility. The study concludes that consistent employer branding that focuses on employees’ needs can enhance work engagement and help organizations retain their employee.